Internet of Everything - A Future Solution? - Damalingam, Nesamalar; Samypen, Yuvarani (Journal of ISMAC, 2026)
The Internet of Everything (IoE) represents a smart interaction between people, data, processes, and objects developed by modern internet technologies. The Internet of Things explains the important connections between these elements, transforming raw data into implemented data. The present survey discusses the Internet of Everything and its enabling technologies for the future of IoE. The key features, including artificial intelligence and machine learning, 6G, and advanced networking, and their use in future technologies are mainly explained in this review article. This research work also describes IoE applications and their future uses, such as smart cities, agricultural changes, advancements in transportation, and innovations in social networks. The challenges of IoE include those in agriculture, industry, education, smart cities, and health care. The review article explains how the Internet of Everything provides solutions for the different challenges and provides researchers with a simple understanding of the current situation, limitations, and future scope of IoE-based systems.